2020
DOI: 10.3390/agronomy10111687
|View full text |Cite
|
Sign up to set email alerts
|

The Herbicidal Potential of Different Pelargonic Acid Products and Essential Oils against Several Important Weed Species

Abstract: There is growing consideration among farmers and researchers regarding the development of natural herbicides providing sufficient levels of weed control. The aim of the present study was to compare the efficacy of four different pelargonic acid products, three essential oils and two natural products’ mixtures against L. rigidum, A. sterilis and G. aparine. Regarding grass weeds, it was noticed at 7 days after treatment that PA3 treatment (pelargonic acid 3.102% w/v + maleic hydrazide 0.459% w/v) was the least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 42 publications
6
42
1
1
Order By: Relevance
“…Thus, to prcevent external factors from affecting the efficacy of the test preparations, prior trials on climate conditions, weed size and application rate were performed (data not shown). Overall, the findings were consonant with published studies 14–17 . Accordingly, the trials were done under moderate climate conditions (approximately 23/18°C day/night), and on medium sized (18–20 cm) weeds.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, to prcevent external factors from affecting the efficacy of the test preparations, prior trials on climate conditions, weed size and application rate were performed (data not shown). Overall, the findings were consonant with published studies 14–17 . Accordingly, the trials were done under moderate climate conditions (approximately 23/18°C day/night), and on medium sized (18–20 cm) weeds.…”
Section: Discussionsupporting
confidence: 89%
“…It showed the best weed control (Figures 2–5) and does not need any formulation (Table 2), being relatively easy to co‐formulate with other herbicidal substances 51 . Co‐formulation should be further studied, for example A3 and the triketone leptospermone, which showed good efficacy in combination with PA in the spray tank 14 . The biological outcome for A3 is equal, or even superior, to the PA herbicide applied (Figure 6), but this outstanding efficacy was achieved with 50 L of product and a water volume of 450 L ha −1 , a reduction of 80 L ha −1 of product and 420 L ha −1 of water in comparison with the benchmark label recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelargonic acid (two times) was characterized by lower efficacy on E. crus-galli. This result agrees with the findings of Travlos et al (2020b), who reported low efficacy of pelargonic acid on grass weeds. Mowing did not reduce E. crus-galli biomass compared with the untreated in both years and evaluations.…”
Section: Resultssupporting
confidence: 93%
“…As for C. album, the double pelargonic acid application reduced its dry weight compared with barley residues and the untreated in both evaluations of 2018 to 2019 and 2019 to 2020 (Figure 1B). The efficacy of pelargonic acid on broadleaf weeds has recently been recently highlighted (Travlos et al 2020b). Mowing reduced C. album dry weight compared with cover crop residues and the untreated in both years and evaluations.…”
Section: Resultsmentioning
confidence: 99%